Vitamin B12, folate, and homocysteine in metabolic syndrome: a systematic review and meta-analysis - Ulloque-Badaracco, Juan R.; Hernandez-Bustamante, Enrique A.; Alarcon-Braga, Esteban A.; Al-kassab-Córdova, Ali; Cabrera-Guzmán, Juan C.; Herrera-Añazco, Percy; Benites-Zapata, Vicente A. (Frontiers in Endocrinology, 2023)
Background & aims: Metabolic syndrome (MetS) is associated with life-threatening conditions. Several studies have reported an association of vitamin B12, folic acid, or homocysteine (Hcy) levels with MetS. This systematic review and meta-analysis assessed the association of vitamin B12, folic acid, and Hcy levels with MetS. Methods: PubMed, Scopus, Embase, Ovid/Medline, and Web of Science were searched up to February 13, 2023. Cross-sectional, case-control, or cohort studies were included. A random-effects model was performed using the DerSimonian and Laird method to estimate the between-study variance. Effect measures were expressed as odds ratios (OR) with their corresponding 95% confidence intervals (95% CI). Between-study heterogeneity was evaluated using Cochran’s Q test and the I2 statistic. Results: Sixty-six articles (n = 87,988 patients) were included. Higher vitamin B12 levels were associated with MetS (OR = 0.87; 95% CI: 0.81–0.93; p < 0.01; I2 = 90%). Higher Hcy levels were associated with MetS (OR = 1.19; 95% CI: 1.14–1.24; p < 0.01; I2 = 90%). Folate levels were not associated with MetS (OR = 0.83; 95% CI: 0.66–1.03; p = 0.09; I2 = 90%). Conclusion: Higher vitamin B12 levels were associated with reduced risk of MetS, whereas higher Hcy levels were associated with MetS. Studies assessing the pathways underlying this association are required.